Pathways of floating marine debris in Jakarta Bay, Indonesia. (August 2021) - Iskandar, Mochamad Riza; Surinati, Dewi; Cordova, Muhammad Reza; Siong, Kian
Abstract: Jakarta is the capital of Indonesia with a high population density, which affects the amount of waste generated. The waste that ends up in Jakarta Bay has become an environmental problem. Understanding the pathway of marine debris in the ocean is important to identify the mitigation strategies. Before this study, the pathways and sources of marine debris in Jakarta Bay were unknown. By using virtual floating marine debris particles in a high-resolution ocean model, the fate of marine debris based on the pathways of particles released in Jakarta Bay in both forward and backward tracking experiments was analyzed. It was found that most of the particles from Jakarta Bay flow toward the Indian Ocean in all seasons. They flow off through the Sunda Strait and reach the open Indian Ocean after a few weeks. With regard to the source location, most particles that end up in Jakarta Bay come from the north of Java Island locally and from the Gulf of Thailand, Sumatra, and Kalimantan coasts. The particles do not appear to vary significantly across all seasons and identifying the pathway of marine debris might be useful in pollution reduction. Highlights: Pathway of floating marine debris into the ocean from Jakarta Bay was investigated. Pathway obtained from combination of surface drifters and ocean model simulations The fate of marine debris based using forward and backward tracking experiments Debris from Jakarta Bay is predominantly heading the Indian Ocean in all seasons. Debris ended up in Jakarta Bay mostly comes locally from the north of Java Island.